Analysis Of Village SDGS System In Sustainable Development In Loloana'a Gido Village, Gido District, Nias Regency - Kasiaman Waruwu; Sophia Molinda Kakisina; Martha Surya Dinata Mendrofa (UNIVED Press, 2024)
The phenomena that occurred at the research location were as follows: 1) lack of active participation of village communities in the development process; 2) lack of basic infrastructure development such as roads, electricity, and internet access is very important for village progress; 3) lack of sustainable management of natural resources to protect the environment and ensure the availability of resources for future generations. The purpose of this research is to find out how the Village SDGs System and sustainable development in Loloana'a Gido Village, Gido District, Nias Regency. The research approach used in this study is a qualitative approach. The data collection techniques used are observation, documentation and interviews. And the data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Based on the results of the interview above, it can provide an explanation of the Analysis of the Village SDGs System in Sustainable Development in Loloana'a Gido Village, Gido District, Nias Regency. Analysis of the Village SDGs system is an important approach to understanding the objectives of SDGs can be implemented in an integrated manner at the village level.